POINT VORTEX DYNAMICS FOR COUPLED SURFACE/INTERIOR QG AND PROPAGATING HETON CLUSTERS IN MODELS FOR OCEAN CONVECTION - Lim C.C.; Majda A.J. (My University, 2001)
The dynamic behavior of baroclinic point vortices in two-layer quasigeostrophic flow provides a compact model for studying the transport of heat in a variety of geophysical flows including recent heton models for open ocean convection as a response to spatially localized intense surface cooling. In such heton models, the exchange of heat with the region external to the compact cooling region reaches a statistical equilibrium through the propagation of tilted heton clusters. Such tilted heton clusters are aggregates of cyclonic vortices in the upper layer and anti-cyclonic vortices in the lower layer which collectively propagate almost as an elementary tilted heton pair even though the individual vortices undergo shifts in their relative locations. One main result in this paper is a mathematical theorem demonstrating the existence of large families of long-lived propagating heton clusters for the two-layer model in a fashion compatible to a remarkable degree with the earlier numerical s...